Omega-3 Fatty Acid Modifies Serum HSP 70 and hs-CRP in Patients With Cardiovascular Disease: Randomized Double‐Blind Placebo-Controlled Trial - Simin Samavat; Mahmoud Djalali; Ebrahim Nematipour; Mohammad Reza Eshraghian; Mahnaz Zarei; Sanaz Gholamhoseini; Mohammad Hassan Javanbakht (Acta Medica Iranica, 2018)
All stages of initiation and progression of atherosclerosis are associated with inflammatory responses. Heat shock proteins (HSP-70) can play an important role in the pathogenesis of atherosclerosis. Serum High-sensitivity C-reactive protein (hs-CRP) is significantly associated with the severity of coronary arteriosclerosis. Omega 3 fatty acids contribute to the primary and secondary prevention of cardiovascular disease (CVD). The purpose of the current study was to assess the effect of omega-3 on serum HSP-70 and HsCRP in patients with atherosclerosis. The current study was a randomized, placebo-controlled, double-blind parallel-group clinical trial, involving 42 male patients with coronary artery disease (CAD). The volunteers were randomly allocated into two groups to receive 4 g omega-3 (containing 720 mg EPA plus 480 mg DHA) supplements (n=21) or placebo (n=21) per day for 8 weeks. Fasting blood samples were taken at the beginning and end of the trial to quantify serum levels of HSP-70 and hsCRP concentrations. The result of the present study revealed that no significant difference was observed between two groups before and after the intervention in terms of serum levels of Cholesterol, Triglyceride, FBS, serum Insulin and homeostasis model of assessment-insulin resistance (HOMA-IR). The difference of HSP-70 between two groups was statistically significant (P=0.04). There was no significant difference between two groups for hsCRP. The study showed that taking omega-3 fatty acids can ameliorate serum HSP-70 as inflammatory parameters. The results suggest more investigation to assess the pathway omega-3 leads to lower incidence of CVD.